Safety assessment of a standardized cucumber extract (Q-Actin™): Oral repeat-dose toxicity and mutagenicity studies. (2018) - Kothari, S.; Saravana, M.; Muthusamy, S.; Mozingo, A.; Soni, M.
Abstract: Cucumus sativus (cucumber) is one of the most widely consumed fruit vegetables worldwide. Recent discovery of iminosugars in commonly consumed fruits and vegetables has promoted the interest in isolating these compounds and understanding the potential benefits to human health. The objective of the present study was to investigate the general toxicity and mutagenic effects of an aqueous extract of cucumber (Q-Actin), standardized to ≥1% (1–2%) ido-BR1 iminosugar. Single dose of Q-Actin was well tolerated without mortality at 2000 mg/kg body weight (bw) in Sprague Dawley rats. Oral (gavage) administration of Q-Actin up to 1000 mg/kg bw/day was well tolerated followed by repeated administration for a maximum period of 90 days in Sprague-Dawley rats. There were no treatment related changes in clinical observations, ophthalmic examinations, body weights and body weight gains or feed consumption, clinical chemistry and pathological changes compared to control. The mutagenicity as evaluated by Ames assay, in vitro chromosomal aberration test and in vivo micronucleus assay did not reveal any potential of Q-Actin to induce genotoxicity. The results showed that Q-Actin is well tolerated in general toxicity studies and did not induce mutagenicity. The no-observed-adverse-effect level (NOAEL) of the standardized aqueous cucumber extract (Q-Actin) is considered to be ≥1000 mg/kg bw/day, followed by repeated administration for90 days.